Pengaruh Sumber Karbon dan Kondisi Inkubasi terhadap Pertumbuhan Kultur In Vitro Purwoceng (Pimpinella pruatjan Molk.) - Roostika, Ika; Purnamaningsih, Ragapadmi; Noviati, Arief V. (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2008)
Pruatjan (Pimpinella pruatjan Molk.) is an Indonesianmedicinal plant which is categorized as endangeredplant and included in Appendix I based on CITES. The invitro conservation techniques have been studied. However,the storage period was very short (4 months) when plantgrowth retardant and media dilution were applied. Besidethat, the residual effect of growth retardant was strongenough so that it needed more than 4 months for recovery.Thus, the use of certain carbon source may prolong thepreservation period with shorter time for recovery. Theobjective of the study was to know the effects of carbonsources (sucrose and mannitol) and culture conditions (cultureroom and growth chamber) to the growth of pruatjancultures. This application was hoped to prolong preservationperiod of pruatjan longer than 4 months and to cut therecovery period after presservation. The study was conductedat Tissue Culture Laboratory in Indonesian Center forAgricultural Biotechnology and Genetic Resources Researchand Development from August 2006 to July 2007. Theactivities included propagation of in vitro shoot grown invitro as explants source, preservation of in vitro shoots ofpruatjan, and regeneration of the cultures after preservation.The experiment was designed as factorial in RandomizedCompletely Block Design with 6 replications. The DKW basalmedia containing 1 ppm BA, 0.2 ppm thidiazuron, and 100ppm arginine were supplemented with mannitol or sucroseat the level of 1, 2, 3, 4, and 5%. The observed variables weretotal number of leaves, number of shoot, and number of wiltleaves. The result revealed that pruatjan cultures could bestored longer than 4 months. Generally, the effect ofmannitol or sucrose was more dominant than that of culturescondition. The mannitol (1-5%) strongly inhibited thegrowth of pruatjan cultures so that only a few culturessurvived at 7 months preservation period and needed about1 month for recovery. On the contrary, the effect of sucrose(at the same level) was better than mannitol. The 2.5%sucrose optimally inhibited pruatjan cultures. At that condition,the cultures could be stored for 10 months withoutmorphological changes so that they could recover spontaneously.